Peripheral CD8 effector-memory type 1 T-cells correlate with outcome in ipilimumab-treated stage IV melanoma patients. (March 2017) - Wistuba-Hamprecht, Kilian; Martens, Alexander; Heubach, Florian; Romano, Emanuela; Geukes Foppen, Marnix; Yuan, Jianda; Postow, Michael; Wong, Phillip; Mallardo, Domenico; Schilling, Bastian; Di Giacomo, Anna Maria; Khammari, Amir; et al.
Abstract: The role of the assessment of peripheral T-cell phenotypes in predicting overall survival (OS) after ipilimumab treatment is unclear. Here, we analysed mononuclear cells in the blood before and at different time points during treatment with ipilimumab in 137 late-stage melanoma patients. The proportions of baseline naïve and memory T-cells were measured by flow cytometry and correlated with OS, with an emphasis on PD-1 expression. High frequencies (>13%) of CD8 effector-memory type 1 (EM1) T-cells at baseline correlated with longer OS (p = 0.029) and higher clinical response rates (p = 0.01). The frequency of these EM1 cells and the M category had independent impacts on OS (hazard ratio = 1.5, p = 0.033; and hazard ratio = 1.9, p = 0.007). In contrast, high baseline frequencies of late stage-differentiated effector memory CD8 cells (>23.8%) were negatively associated with OS (p = 0.034) but did not correlate with clinical response. Following treatment, a decrease of CD8 cells from baseline to the time of the second drug dose and at later time points was strongly and consistently correlated with a high clinical response rate. Our observations thus suggest an important predictive role of baseline CD8 EM1 cells and changes in CD8 cells for clinical response of ipilimumab. Further validation of these biomarker candidates is warranted. Highlights: Analysis of circulating T-cell memory compartment in melanoma at baseline of ipilimumab. Higher levels of CD8 EM1 cells in blood are predictive for good outcome. Low abundance of peripheral CD8 TEMRA cells associate with good outcome. Decreasing cells correlated with response following the ipilimumab treatment.